PENGARUH PEMBELAJARAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA - REZA FAHMI; TRI AMANDA (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". This paper starts from the fact that, in spite of entrepreneurial learning materials have been taught in the lecture material at IAIN Imam Bonjol Padang. But the number of students interested in entrepreneurship is still very limited. Further research using quantitative methods. Data analysis techniques are linear regression analysis. The independent variable is entrepreneurial learning, and the dependent variable is the interest in entrepreneurship. The population in this study: Manajemen Dakwah students. Result: there is significant entrepreneurial learning on student interest in entrepreneurship.